2005
DOI: 10.1007/s00259-005-1840-x
|View full text |Cite
|
Sign up to set email alerts
|

To use MIBI or not to use MIBI? That is the question when assessing tumour cells

Abstract: 99mTc-sestamibi (MIBI) is a well-known tumour imaging agent. Its retention within tumour cell mitochondria is related to perfusion and to the magnitude of the electrical gradient, reflecting cell viability. Several internal cell factors modulate this uptake; for example, multidrug resistance membrane proteins (Pgp and MRP1) and anti-apoptotic BCl-2 protein of the outer mitochondrial membrane can limit retention of MIBI. At the early stage of cell apoptosis, the electrical driving forces of MIBI uptake are impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 48 publications
0
41
0
5
Order By: Relevance
“…The absence or reduction of 99m Tcsestamibi uptake on early images may suggest that 99m Tcsestamibi uptake can also be influenced by other factors, rather than simply Pgp activity. Inefficient blood supply, advanced cell necrosis, hypoxia and the overexpression of the apoptotic protein Bcl-2 may significantly reduce the uptake of 99m Tc-sestamibi in tumour lesions [52]. Aloj et al [53] found a significant correlation between the absence of 99m Tc-sestamibi uptake and overexpression of Bcl-2 in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The absence or reduction of 99m Tcsestamibi uptake on early images may suggest that 99m Tcsestamibi uptake can also be influenced by other factors, rather than simply Pgp activity. Inefficient blood supply, advanced cell necrosis, hypoxia and the overexpression of the apoptotic protein Bcl-2 may significantly reduce the uptake of 99m Tc-sestamibi in tumour lesions [52]. Aloj et al [53] found a significant correlation between the absence of 99m Tc-sestamibi uptake and overexpression of Bcl-2 in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…MIBI reversibly passes into the cytoplasm via thermodynamic driving forces and irreversibly passes into the mitochondria using the electrical gradient generated by a high negative inner transmembrane mitochondrial potential (28)(29)(30). Accordingly, more intense MIBI concentrations have been found in malignant tumor cells than in normal cells because of the higher electrical gradient of the former (28).…”
mentioning
confidence: 99%
“…The mechanism of cellular radiopharmaceutical accumulation has been reported to depend on the size of a tumor, the blood flow within it (28), and the richness of mitochondria in the tumor cells (28,29). MIBI reversibly passes into the cytoplasm via thermodynamic driving forces and irreversibly passes into the mitochondria using the electrical gradient generated by a high negative inner transmembrane mitochondrial potential (28)(29)(30).…”
mentioning
confidence: 99%
“…The mechanism of Tc-99m MIBI accumulation in tumor has been reported to depend on the size of a tumor, the blood flow and the richness of mitochondria in the tumor cells (Moretti et al, 2005;Piwnica-Worms et al, 1994;Saggiorato et al, 2009). MIBI irreversibly passes into the mitochondria using the electrical gradient generated by a high negative inner transmembrane mitochondrial potential of malignant cells (Chernoff et al, 1993;Moretti et al, 2005;Piwnica-Worms et al, 1994). Also, there is a report that TSH simulates both F-18 FDG PET and Tc-99m MIBI uptake in poorly differentiated papillary thyroid cancer in vitro experiment (Kim et al, 2009).…”
Section: Tc-99m Methoxyisobutylisonitrile (Tc-99m Mibi)mentioning
confidence: 99%